Heterologous synthesis of 4-ethylphenol in engineered Escherichia coli. (September 2020) - Zhang, Ying; Long, Liangkun; Ding, Shaojun
Graphical abstract: Artificial 4-ethylphenol biosynthetic pathway constructed in Escherichia coli from glucose or glycerol. Abbreviations: TAL: tyrosine ammonia lyase; PAD: phenolic acid decarboxylase; VPR: vinylphenol reductase; Amp R, ampicillin resistance. Highlights: An artificial biosynthesis pathway of 4-ethylphenol was constructed in E. coli . This is the first report of 4-ethylphenol biosynthesis from renewable substrates. Optimization was performed for improving enzyme expression and 4-ethylphenol production. 110 mg/L 4-ethylphenol was produced in Terrific Broth (TB) medium with glycerol in flask cultivation. Abstract: 4-Ethylphenol (4-EP) is an industrially versatile commodity chemical widely applied in the pharmaceutical and food industries. In this study, an artificial biosynthetic pathway was constructed in Escherichia coli for production of 4-ethylphenol from simple sources of carbon. The pathway consists of the tal, pad and vpr genes, which encode tyrosine ammonia lyase (TAL), phenolic acid decarboxylase (PAD) and vinylphenol reductase (VPR), respectively. Our results confirmed that the TAL from Saccharothrix espanaensis possessed higher catalytic activity than the TAL from Rhodobacter sphaeroides for biosynthesis of p -hydroxycinnamic acid. The low solubility of Lactobacillus plantarum VPR (LpVPR) in E. coli was a critical factor limiting its availability in the biosynthetic pathway. The solubility of LpVPR was improved by E. coli strain and induction condition optimization. Under the optimized conditions, the engineered E. coli TransB-TPV produced as high as 110 mg/L 4-EP at 37 ℃ in Terrific Broth (TB) medium with glycerol as carbon source after cultivation of 48 h. This study provided a new and feasible strategy for biosynthesis of 4-EP from simple sugars, which may provide a basis for future large-scale industrial application.